Renal liposarcoma: case report and review of systemic treatment - Rioja, P (2021)
Liposarcomas are malignant mesenchymal tumours usually located in the retroperitoneum, rarely occurring as a single lesion in the kidney. We present a case of a 59-year-old male patient with a left renal mass detected by computed tomography scan. He underwent radical nephrectomy and the histopathological study reported a primary undifferentiated liposarcoma of the kidney without nodal involvement. After 15 months of surgery, he remained asymptomatic and without evidence of disease recurrence. The objective of this report is to present a case and literature review with current evidence of treatment options and prognostic factors for survival.